1984
DOI: 10.1136/jnnp.47.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Why do bridging veins rupture into the virtual subdural space?

Abstract: SUMMARY Electron microscopic data on human bridging veins show thin walls of variable thickness, circumferential arrangement of collagen fibres and a lack of outer reinforcement by arachnoid trabecules, all contributory to the subdural portion of the vein being more fragile than its subarachnoid portion. These features explain the laceration of veins and the subdural location of resultant haematomas.Most subdural haematomas due to venous bleeding have been attributed to lacerations in bridging veins. These vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
111
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(119 citation statements)
references
References 8 publications
3
111
0
5
Order By: Relevance
“…In some cases, subdural haematomas appear to be isolated, with no other apparent signs, making diagnosis difficult. We would like to stress the need for careful vertex screening to look for bridging vein thrombosis, which-as some pathologists have pointed out-has high diagnostic value [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, subdural haematomas appear to be isolated, with no other apparent signs, making diagnosis difficult. We would like to stress the need for careful vertex screening to look for bridging vein thrombosis, which-as some pathologists have pointed out-has high diagnostic value [1].…”
mentioning
confidence: 99%
“…They extend, bridge-like, at intervals along the midline, from their attachment to the arachnoid at the medial border of the cerebral hemispheres to the superior sagittal sinus of the dura mater, into which they flow after having traversed the arachnoid space and the deep layers of the dura mater [2]. These veins constitute a short, non-tortuous, perpendicular pipeline between the arachnoid and the dura, making them particularly vulnerable to rupture during anteroposterior movements of the brain within the cranium [1]. In the absence of a clotting disorder, such ruptures lead to thrombosis within a few hours (Fig.…”
mentioning
confidence: 99%
“…Köprü venlerinin özellikle subdural bölgede yırtılmaya meyilli olması, subaraknoid bölgedeki venlere göre daha az kollajen lif içermesine ve içinden geçtiği duranın sert olmasına bağlanmaktadır (15).…”
Section: Discussionunclassified
“…It is classically associated with head trauma rising from rapid acceleration and/or deceleration that produces the rupture of cortical arteries and most often occurs by tearing of bridging veins (BVs) as they cross from the brain surface to the dural sinus [Maxeiner and Wolff 2002]. Fenderson et al [2007] reported that these veins are prone to rupture at the point of their entry into the SSS, and this was confirmed by the results of microscopy examination [Yamashima and Friede 1984;Vignes et al 2007]. They found that, due to the histological composition of the BVs and the change in the collagen pattern in the vein walls near their entrance into the superior sagittal sinus (SSS), the subdural portion of a BV is more fragile than its subarachnoidal portion.…”
Section: Introductionmentioning
confidence: 99%
“…They found that, due to the histological composition of the BVs and the change in the collagen pattern in the vein walls near their entrance into the superior sagittal sinus (SSS), the subdural portion of a BV is more fragile than its subarachnoidal portion. The rupture of BVs is induced by the brain-skull relative motion following a head impact as described by neuropathologists [Yamashima and Friede 1984] and by experimental work conducted in vivo [Willinger et al 1995;Ji et al 2004;Bayly et al 2005;Ji and Margulies 2007;Sabet et al 2008].…”
Section: Introductionmentioning
confidence: 99%